The Role of Information and Communication Technology in UK Primary School: A Case Study - Alsharif, Taghreed (Technium Social Sciences Journal, 2022)
The use of Information and Communication Technology (ICT) tools have been introduced in the learning process of primary school students in the UK with a view to derive several benefits from the IT revolution for students as well as teachers. Using descriptive survey methodology, the present study examines the perceptions of primary school teachers on the role of ICT in primary education in the UK. The survey was conducted at a school in Leeds, and the data were collected through structured interviews conducted with subject teachers, the Head teacher and the IT coordinator at the school. A thematic analysis of the collected data showed that the teaching staff displayed more positive attitude towards the role of ICT in influencing learning among students in UK primary schools compared to last two years. The major concern the teachers raised was that it is difficult for teachers to keep themselves updated on the changes in ICT tools and technologies. However, regular training and seminars were suggested as the solution to the issue.